ANALISIS PENGARUH NET PROFIT MARGIN (NPM), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) DAN CURRENT RATIO (CR) TERHADAP EARNING PER SHARE (EPS) PADA PERUSAHAAN SEKTOR INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Wijayanto, Edi; Rois, Muhammad; Indrasari, Luthfiyah; Widodo, Saniman (KEUNIS, 2022)
This research is based on the problem of the Goods and Consumption Industry Sector Companies that experience Earning Per Share which tends to decrease during the 2016-2020 period. This study aims to determine the significance of the effect of Net Profit Margin, Return On Equity, and Current Ratio on Earning Per Share in Goods and Consumption Industry Sector Companies listed on the IDX. The sample in this study amounted to 7 companies using purpose sampling. The analytical model used in this study is a multiple linear regression analysis model. The results of the t test show that the variables Net Profit Margin, Return On Equity have a significant effect on Earning Per Share, while the Debt to Equity Ratio and Current Ratio variables have no significant effect on Earning Per Share.